Exploring the drivers of irregular spending in the EU cohesion policy: A fractional regression analysis - Francesco Foglia; Francesco Molica; Anabela M. Santos (European Commission, Joint Research Centre (JRC), 2024)
The regularity and legality of EU spending, i.e. the conformity of incurred expenditures with relevant legislation, is an important measure of efficiency. It is also a key pre-condition for the effectiveness of EU funds. The present paper aims to understand the main determinants of irregular spending in EU cohesion policy funding: this is a highly important, yet understudied topic, especially given that cohesion policy is the area of the EU budget with the highest levels of irregularities. Using time series data and a fractional regression analysis model, the study provides evidence that the specific governance and structure of cohesion policy programmes can explain the intensity of irregular spending. Overall, the analysis finds that the higher the complexity of programmes (e.g. in terms of number of priorities, multi-fund focus), the higher the risk of irregularities and difficulty to detect them by programme authorities. The paper also shows the relevant role of specific aspects of the implementation, such as the size and number of projects, in influencing the regularity of expenditures. The results suggest that more simplification, greater thematic concentration and funds' rules harmonization could bring benefits in the future.
Keywords: 330; EU structural funds; EU budget; EU states; EU-Strukturfonds; EU-Haushalt; EU-Staaten